I'M BEGINNING TO REMEMBER: THE SHARP STUDY'S NEIGHBORHOOD APPROACH TO AFRICAN AMERICAN BRAIN HEALTH. (11th November 2018) - Croff, R; Francois, E; Hedmann, M; Towns, J; Pruitt, A; Kaye, J
Abstract: Mild Cognitive Impairment (MCI) may precede dementia; African Americans have disproportionately higher risk of dementia and gentrification. Physical activity and social engagement may mitigate decline; however, gentrification impedes desirability for neighborhood walking and socialization. The Sharing History through Active Reminiscence and Photo-imagery study (SHARP) engages African Americans in a culturally celebratory multimodal intervention blending walking and history. Seven African American triads aged ≥55 (2 cognitively healthy/1 person with MCI) walked 3x/week for 6 months in Portland, Oregon's historically Black neighborhoods. Using a tablet, triads followed 1-mile routes. GPS-triggered historical images prompted reminiscence. Recorded conversations created an oral history archive and informed community health education. The Montreal Cognitive Assessment (MoCA), weight, blood pressure (BP), and a health survey were administered pre/post-study. Focus groups discussed intersections of aging, memory, and place. Thematic analysis guided qualitative interpretation. BP and MoCA scores improved for most participants, including those with MCI. About half experienced weight loss, half weight gain, with mean loss greater than mean gain. Sharing neighborhood memories had a healing effect against the trauma of gentrification. Learning partners' community stories was cognitively stimulating and contributed to increased socializing outside the study. Recording memories within triads with shared sense of community loss gave reason to walk, made walking more meaningful because study deliverables served individual and community needs, and sustained 90% retention. Combining physical activity and social engagement is promising for mitigating cognitive decline. Sustaining behaviors may require framing them within meaningful contexts that resonate with people's historical connections to others, place, and community.